The Kanun-Nama Code of Sarajevo - Đurđev, Branislav (Prilozi za orijentalnu filologiju, 2017)
The code included under No. 1 in the list of kanunnamas and Jetvas of the Oriental Institute consists of many copies of kanun-namas dating from 16 and 17ct. At first sight it seems that this code represents a single work of a scribe who also made a unique division of the code, although he did not carry it out completely. Namely, he first divided the common kanun-namas, then the Bosnian ones and fmally the laws concerning separate legal fields (mining, sa/arija, etc.). On the occasion of issuing (publishing) the mine laws (G.Z.M. 25/1913, 133) F. Spaho said that this code represented single work of one scribe and that it consisted of two parts. The author has found out that the code consists of three parts. Only the first one is a single manuscript, while the second one consists of 5 manuscripts and the third one of 2 manuscripts. The scribe of the code copied only 4 manuscripts (II.1, II.4, III.1 and III.2) while the remaining 4 ones (I, 11.2, II.3 and II.5) he included into the code as already fmished manuscripts. All the manuscripts are a compilation, not only the ones copied from the original but also the others included into this volume. The scribe had begun by copying the maimscript 11.1, but he later put the fmished manuscript I ahead in order to achieve a better arrangement. The author has used an unpublished short description of the manuscript written by Safet-bey Bašagić, but he also gives his own description. He publishes Bašagić's description but he points out that it has not been prepared for printing. He agrees with Bašagić that this code could have been composed in the middle of 18th ct., but he also points to the fact that the four inserted manuscripts must be older. One of them dates from 1688 and the remaining three also date from 17th ct.